Philosophical Shakespeares - Joughin, John J. (Accents on Shakespeare., 2000)
Philosophical Shakespeares focuses on and encourages the growing dissolution of boundaries between literature and philosophy. The approach is interdisciplinary and includes problem-centred readings of particular plays.